Jurisdição de família como forma de efetivação da cidadania - Barone, Lourdes Regina Jorgeti (2013)
The present thesis talks about, in its essence, the jurisdictional way of dealing with family conflicts, having as its main focus the citizenship effectiveness. Addresses the importance of the family, guided by love, affection, consensus, care and respect to the diversity and dignity of its members, as responsible to appreciation, formation and development of the human being. Reinforces the understanding that it is in the family, where happens the total prosecution of the basic rights, effecting in it the real concept of citizenship. Shows the necessity of protecting family as well as using all principles inherent to Social and Democratic State of Law, having as the basic and most important point, the human being dignity. Analysis some different kinds of families that are more common in Brazilian s society, showing first the social, personal, patrimonial and succession effects ,to show afterwards, the position of the Court facing some issues that are not disciplined by the legislation in force. Lists, not only the transformation suffered by the society related to Family Law in the last century, but also to the consequent legal development, always in accordance to the Constitution. Explores the adjudication in force, in all the Country and the way the citizen uses and evaluates it. Reflects about how this adjudication is used in family conflicts, focusing the details of the conflicts, its time and who is involved. Talks about alternative ways of solving conflicts and demonstrates the need to adopting these ways in wide scale in actions involving Family Law, transforming the opponent culture in a composing culture. Furthermore it envisions the Court provision and the legal proposes to mediate reconciliation in family conflicts, having as a goal, to make it easy to the citizens having a different treatment, as an accessible via to guarantee their rights and the guarantees ensured in the Constitution. Beyond that, it suggests adopting in full, the Bill that establishes the Special Family Court as the way of jurisdiction provision more appropriate to family conflicts, according as it uses exactly the alternative ways of solving conflicts to the causes of their competence and enables the participation of a multidisciplinary team, in a structure guided by celerity, competence, and effectiveness of its decisions in full working.